CHANGES IN THE LEVEL OF REGIONAL DEVELOPMENT OF ALBANIA AND VOIVODSHIPS IN POLAND IN 2010-2017 - Kozak, Sylwester; Muça, Etleva (Management and Administration Journal, 2020)
The article presents the results of research on changes in the level of regional development in Albania and in all voivodships (regions) in Poland in 2010-2017. Annual data comes from national statistical offices. The level of regional development was determined by the multi-criteria decision analysis method - SAW (the Simple Additive Weighting) and includes two social and six economic criteria. The obtained results indicate that in the whole analyzed period the level of regional development in Albania was lower than in all regions in Poland. However, it achieved the highest increase in the studied group, among others thanks to improving the demographic situation, increasing entrepreneurship and improving the quality of the market. The Mazowieckie, Pomorskie and Wielkopolskie voivodships were characterized by the highest level of development throughout the entire period as a consequence of a good demographic situation, increased entrepreneurship and high GDP dynamics. Negative population growth and an increase in unemployment meant that the Lubelskie and Warmińsko-Mazurskie voivodships are characterized by the lowest level of regional development in Poland. Faster improvement of the situation in more developed regions contributed to the increase of disparity in the socio-economic development of regions in Poland.